2014
DOI: 10.4111/kju.2014.55.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of the Readjustable Sling Procedure for Female Stress Urinary Incontinence With Intrinsic Sphincter Deficiency or Recurrence

Abstract: PurposeWe evaluated the long-term outcome of a readjustable midurethral sling system (Remeex) in the treatment of recurrence of stress urinary incontinence (SUI) after surgical treatment or SUI with intrinsic sphincter deficiency (ISD).Materials and MethodsThis study included 19 patients who underwent the Remeex procedure with a mean of 45.6 months of follow-up. The patients had responded to a telephone questionnaire. Thirteen patients had ISD, four patients had SUI recurrence, and two patients had both. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The aim of this paper was to evaluate the role of the suburethral tension adjustable sling procedure for the treatment of urinary incontinence due to ISD in a larger series of patients with a longer follow‐up than previously reported in literature. In fact, although the latest papers regarding the Remeex technique, including our experience, have reported cure rates higher than 80%, the small number of patients studied (mainly between 20 and 30 cases) or the rather limited follow‐up periods (not more than 5 years) tended to downsize the importance of these outcomes . A larger series of patients was only published by Errando et al, who showed a cure rate of 86% in 70 patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The aim of this paper was to evaluate the role of the suburethral tension adjustable sling procedure for the treatment of urinary incontinence due to ISD in a larger series of patients with a longer follow‐up than previously reported in literature. In fact, although the latest papers regarding the Remeex technique, including our experience, have reported cure rates higher than 80%, the small number of patients studied (mainly between 20 and 30 cases) or the rather limited follow‐up periods (not more than 5 years) tended to downsize the importance of these outcomes . A larger series of patients was only published by Errando et al, who showed a cure rate of 86% in 70 patients.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, although the latest papers regarding the Remeex technique, including our experience, have reported cure rates higher than 80%, the small number of patients studied (mainly between 20 and 30 cases) or the rather limited follow-up periods (not more than 5 years) tended to downsize the importance of these outcomes. [21][22][23] A larger series of patients was only published by Errando et al, who showed a cure rate of 86% in 70 patients. However, the reported follow-up was less than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tension-free midurethral sling procedures have been used widely for SUI. Owing to the evolution of midurethral slings and their high efficacy and safety, retropubic midurethral slings and transobturator midurethral slings have been introduced into numerous urologic fields [ 3 ]. However, procedures using these 2 slings have a weakness: appropriate tension cannot be determined during the operation.…”
Section: Introductionmentioning
confidence: 99%